Editorial note (2019)
The Revista Colombiana de Ciencias Hortícolas wishes to share the recognition granted by the Departamento para la Indexación de Revistas Científicas Colombianas Especializadas – Publindex (Colciencias) in Announcement 830 of 2018, placing the journal in category B. This significant achievement is indicative of the quality of the journal’s articles, written by different research centers, universities, and companies that provide quality content to the journal.